Evaluation of the depth of the Pantanal sedimentar basin based on seismic events (Research, Society and Development, 2021)
The main objective of this study is qualify the seismic activities captured at the Santo Antônio do Leverger seismic station (SALV), state of Mato Grosso, Brazil. The choice of this station was due to its location in the northern portion of the Pantanal Sedimentary Basin, considered historically as one of the seismogenic regions of Brazil. The methodology involved downloading the files through the poet.py script, where the events were identified, selected and stored within 440 km from the SALV station. Once confirmed, filtrations were applied using the Butterworth method. This method minimizes the loss of information recorded by events that have occurred. Thus, most events indicate disagreement with the applied filters, demonstrating that there is a structure that influences the propagation of the wave, changing its original speed and frequency. The triggering method was applied to the behavior of seismic waves that crossed the sedimentary interval of the Pantanal Basin. The results were plotted on maps, overlaid in the form of sub-regions of the Pantanal using the QGIS geoprocessing software, in which the geological contacts were determined. Thus, it was possible to observe that each sub-region presents a different profile for each event, with sub-regions that tend to increase the signal's acceleration, maintain it or slow it down.